Literatur Review Peran Dukungan Keluarga pada Pasien Pasca Stroke dalam Latihan Rehabilitasi Medik - Rahma Rufaida Susetyo (Pusat Riset dan Inovasi Nasional, 2023)
Introduction: According to the Indonesian Medium-Term Development Plan IV for the year 2020 - 2024, stroke is ranked as the top disease in Indonesia, with a 93.4% increase from the previous period. Additionally, data from the 2018 Riskesdas P2TM shows that out of 3 individuals who experienced a stroke, 2 of them suffered disabilities. Objective: To analyze the role of family support in post-stroke patients' engagement in medical rehabilitation exercises. Method: This study utilized data from a literature review based on previous research. High-quality secondary data sources such as Google Scholar, Mendeley, and Research Gate were used to search for data in the literature review. These databases facilitate access to reputable journals as the primary references. Results: Based on the analysis of 5 journals conducted by various researchers, it was found that family support plays a significant role in motivating post-stroke patients to engage in medical rehabilitation exercises. Conclusion: There is a correlation between family support and the motivation of post-stroke patients to participate in medical rehabilitation exercises. Families serve not only as sources of social support but also actively encourage and motivate patients to achieve optimal recovery levels.